2018
DOI: 10.1111/and.13220
|View full text |Cite
|
Sign up to set email alerts
|

Seminal exosomes and HIV‐1 transmission

Abstract: Exosomes are endosomal‐derived membrane‐confined nanovesicles secreted by many (if not all) cell types and isolated from every human bodily fluid examined up to now including plasma, semen, vaginal secretions and breast milk. Exosomes are thought to represent a new player in cell‐to‐cell communication pathways and immune regulation, and be involved in many physiological and pathological processes. Susceptibility to HIV‐1 infection can be impacted by exosomes, while HIV‐1 pathogenesis can alter exosomal functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 62 publications
0
27
0
1
Order By: Relevance
“…Therefore, functional analyses based entirely on the cell line-derived exosomes can be misleading and require re-evaluation in patient material. This shows a strong need to standardize protocols used for exosome isolation and analysis from biologically relevant bodily fluids, such as blood [15], urine [16], breast milk [17], cerebrospinal fluid (CSF) [18], saliva [19], human semen [20], and synovial fluid [21]. All these different sources of exosomes require meticulous analysis, which will result in the decision of the best criteria for the exosome isolation method as well as further exosome analysis.…”
Section: Source and Methods Of Isolation For Proteomic Analysismentioning
confidence: 99%
“…Therefore, functional analyses based entirely on the cell line-derived exosomes can be misleading and require re-evaluation in patient material. This shows a strong need to standardize protocols used for exosome isolation and analysis from biologically relevant bodily fluids, such as blood [15], urine [16], breast milk [17], cerebrospinal fluid (CSF) [18], saliva [19], human semen [20], and synovial fluid [21]. All these different sources of exosomes require meticulous analysis, which will result in the decision of the best criteria for the exosome isolation method as well as further exosome analysis.…”
Section: Source and Methods Of Isolation For Proteomic Analysismentioning
confidence: 99%
“…EVs from infected cells are able to activate other cells DENV (Velandia-Romero et al, 2020;Mishra et al, 2019) RNAs inside EVs related to host responses to infection DENV (Martins et al, 2018a), H5N1 (Maemura et al, 2018;Maemura et al, 2020), HBV (Zhao X. et al, 2019), HIV (Bernard et al, 2014), HSV-1 (Han et al, 2016;Huang et al, 2019), influenza (Liu Y. et al, 2019), Rabies (Wang et al, 2019a), RSV (Chahar et al, 2018), West Nile (Slonchak et al, 2019) EVs from infected cells can trigger the secretion of proinflammatory molecules in other cells HIV (Sampey et al, 2016;Mukhamedova et al, 2019), H5N1 (Maemura et al, 2018;Maemura et al, 2020), HBV (Zhao X. et al, 2019), RSV (Chahar et al, 2018) EVs involved in IFN-mediated responses DENV (Martins et al, 2018), HBV (Yao et al, 2019;Zhao X. et al, 2019), HCV (Dreux et al, 2012;Okamoto et al, 2014), HIV-1 (Khatua et al, 2009), HSV-1 (Huang et al, 2019), influenza EVs that can restrict viral replication Rabies (Wang et al, 2019a), HBV (Zhao X. et al, 2019), HIV (Ouattara et al, 2018), Induction of massive inflammatory responses/vascular permeability DENV (Sung et al, 2019) EVs can block/impair viral propagation Enterovirus (Chen et al, 2015), Influenza (Liu Y. et al, 2019), HIV-1 (Khatua et al, 2009), HSV-1 (Han et al, 2016;Deschamps and Kalamvoki, 2018;Huang et al, 2019), Rabies…”
Section: Mechanism Virusmentioning
confidence: 99%
“…They can directly inhibit HIV-1 cellular entry, prevent transmission of HIV from vaginal epithelial cells to monocytes, T lymphocytes and PBMCs. They can also inhibit replication after internalization by blocking reverse transcriptase activity and inhibiting binding of transcription factors to the HIV1 promoter (Ouattara et al, 2018). This helps to explain the low infection rates of people exposed to the virus (Ouattara et al, 2018;Welch et al, 2019).…”
Section: Mechanism Virusmentioning
confidence: 99%
“…Reports suggest that exosomes from healthy individuals inhibit HIV-1 replication by blocking viral RNA reverse transcription. Exosomes secreted from the cells and secreted in biological fluids-semen [87][88][89], vaginal fluids [78], and breast milk [90]-suppress HIV-1 replication. Researchers have reported that HIV-1 replication is blocked by semen and vaginal exosomes at the post-entry stage before integration (e.g., reverse transcription level) [78,89].…”
Section: Semen Vaginal Fluids Breast Milk and Other Biological Fluidsmentioning
confidence: 99%
“…Furthermore, an abundance of plasma exosomes and the size of exosomes correlate inversely with CD4 counts and correlate positively with CD8T cell counts, thus indicating HIV disease progression [63]. On the other hand, as the EVs, particularly exosomes, derived from semen [87][88][89], vaginal fluids [78], and breast milk [90] have been identified as inhibitory to HIV, these exosomes could be used as a potential therapy against HIV infection. These EVs have protective properties that can restrain vertical and horizontal viral transmission.…”
Section: Future Perspectives On Evs In Hiv Infection and Wound Healingmentioning
confidence: 99%